Do Microsurgical Outcomes Differ Based on Which Specialty Does the Operation? A NSQIP Analysis - Zhang, Jacques X. (Plast Reconstr Surg Glob Open, 2020)
BACKGROUND: Because plastic surgeons do not “own” a specific anatomic region, other surgical specialties have increasingly assumed procedures historically performed by plastic surgery. Decreased case volume is postulated to be associated with higher complication rates. Herein, we investigate whether volume and surgical specialty have an impact on microsurgical complications, specifically surgical site infection (SSI) and reoperation rates. METHODS: The 2005–2015 National Surgical Quality Improvement Program participant use file was queried by Current Procedural Terminology code for breast and head/neck microsurgeries. Multivariate logistic regression was performed to compare the outcomes between surgical specialties. A cumulative frequency variable was introduced to investigate the effect of case volume on complication rates. RESULTS: We captured 6,617 microsurgical cases. Multivariate logistic regression revealed that although the rate of SSI was lower in plastic surgery compared with otolaryngology for head and neck reconstructions (13.3% versus 10.5%) and compared with general surgery for breast reconstructions (5.4% versus 4.7%), there was no significant difference between specialties (P = 0.13; P = 0.96). Increased case volume is negatively correlated with complications. CONCLUSIONS: Plastic surgery is at risk given case cannibalization by other specialties. We conclude that surgical specialty does not affect the rates of SSI and reoperation. We demonstrate a correlation between lower volumes and increased complications, implying that, once a specialty has amassed critical case experience, complication rates may decrease, and outcomes can be equivalent or superior. Case breadth and volumes should be maintained to preserve skills, optimize outcomes, and maintain the specialty as it currently exists.